2021
DOI: 10.1155/2021/8427575
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Direct Position Determination via the Dimension Reduction Method for Noncircular Signals

Abstract: This work studies the direct position determination (DPD) of noncircular (NC) signals with multiple arrays. Existing DPD algorithms of NC sources ignore the impact of path propagation loss on the performance of the algorithms. In practice, the signal-to-noise ratios (SNRs) of different observation stations are often different and unstable when the NC signal of the same radiation target strikes different observation locations. Besides, NC features of the target signals are applied not only to extend the virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…See Table 2 for other simulation parameters. Moreover, to show the heteroscedasticity of the received SNR at each observation station [36], we define 3 and M = 8 in Figure 4. The spectral peak diagrams show that NC-Euler-WESPRIT algorithm can successfully distinguish the targets even when the number of array elements at each observation station is less than that of targets.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…See Table 2 for other simulation parameters. Moreover, to show the heteroscedasticity of the received SNR at each observation station [36], we define 3 and M = 8 in Figure 4. The spectral peak diagrams show that NC-Euler-WESPRIT algorithm can successfully distinguish the targets even when the number of array elements at each observation station is less than that of targets.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Studies by Mohammad and other scholars have shown that the DPD method has better positioning performance than the two-step method multipath and low SNR scenarios [5,6]. Direct positioning technology discretizes the space where the radiation source may exist.…”
Section: Introductionmentioning
confidence: 99%